Multi‐informant reports of depressive symptoms and suicidal ideation among adolescent inpatients. Issue 1 (5th October 2021) - Augenstein, Tara M.; Visser, Katherine F.; Gallagher, Katie; De Los Reyes, Andres; D'Angelo, Eugene J.; Nock, Matthew K.
Abstract: Objective: Suicide is a leading cause of death among adolescents, and suicidal thoughts represent key predictors to suicidal behavior. Yet, suicidal thoughts can be challenging to accurately assess. Symptoms that commonly co‐occur with suicidal thoughts, such as depressive symptoms, may provide valuable information for predicting these thoughts. Although clinicians commonly collect multi‐informant reports about adolescent depressive symptoms, these reports often yield discrepant findings as individual predictors of adolescents' suicidal thoughts. Method: We tested the ability of specific patterns of multi‐informant reports to predict adolescents' suicidal thoughts. Ninety adolescent inpatients and their parents (i.e., "dyads") reported on adolescent depressive symptoms, and adolescents completed self‐report assessments of suicidal thoughts at baseline and three‐month follow‐up. Results: Dyads displayed variability in reporting patterns, and these patterns uniquely predicted suicidal thoughts. Adolescents reporting elevated depressive symptoms displayed increased concurrent suicidal thoughts relative to adolescents reporting subthreshold depressive symptoms, regardless of parent report. Yet, only adolescents who reported elevated depressive symptoms and whose parents reported subthreshold adolescent depressive symptoms displayed increased future suicidal thoughts. Conclusions: Identifying patterns of multiple informants' reports about adolescent depressive symptoms may improve the prediction of suicidal thoughts. These findings have important implications for assessing adolescents at risk for suicide.